PENGARUH PERTUMBUHAN PERUSAHAAN, AUDIT TENURE DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN - Pratiwi, Laras; Lim, Tri Hadrianto (Program Studi Akuntansi, Universitas Kuningan, 2018)
The going concern audit opinion can used by stakeholders to predict the bankruptcy of a company, therefore the auditor should be responsible of his opinion. This study aims to obtain empirical evidence of the influence company growth, audit tenure and audit opinion of the previous year to going concern audit opinion. Population in this research using data manufacturing companies wich listed on the Indonesia Stock Exchange period 2013-2017. Method of Sampling is purposive sampling. Total sample are 22 companies. Research method using logistic regression analysis model. The results show that company's growth and the previous year's audit opinion affect to going concern audit opinion, while audit tenure doesn't affect to going concern audit opinion.Keywords : Growth, Audit tenure, Going Concern Opinion